Test Anxiety During Formative Assessment in English Learning: Insights from Islamic Boarding School Students - Bukhori, Bukhori; Herlinda, Silvi; Putriani, Zelly; Maulana, M.Faisal; Haq, Muhammad Valiyyul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study investigates test anxiety among students at Aek Hayuara Sibuhuan Islamic Boarding School during formative assessments in English learning and explores the factors contributing to their anxiety. Employing a qualitative case study approach, the research selected participants through purposive sampling. Data collection methods included closed-ended questionnaires and interviews. The findings reveal that the majority of students experience test anxiety, which manifests in two key dimensions: emotionality and worry. Furthermore, four primary factors contribute to this anxiety: fear of failing the course, psychological distress, poor study skills, and low self-esteem.